EFFECTIVENESS OF BIOTECHNOLOGY E-MODULES WITH THE SETS APPROACH ON NINTH GRADE STUDENTS’ PROBLEM-SOLVING SKILLS - Nila Permatasari; Sajidan Sajidan; Umi Fatmawati (Universitas Bhinneka PGRI, 2026)
This study aims to investigate the effectiveness of using biotechnology e-modules for eco-enzyme production, based on the SETS (Science, Environment, Technology, and Society) approach, on the problem-solving skills of ninth-grade junior high school students. A quasi-experimental design with a non-equivalent control group was employed. The sample consisted of two classes, each comprising 32 students, divided into an experimental class and a control class. The main instrument was a problem-solving skills test based on Polya’s indicator. Data were analyzed using ANCOVA after confirming the assumptions of normality and homogeneity of variance. The results revealed a significant difference between the average posttest scores of the experimental class (80.562) and the control class (46.094), with a significance level of 0.000 (p 0.05). The R² value of 0.952 indicates a powerful influence of the e-module on the improvement of problem-solving skills. This e-module facilitates students’ contextual understanding of biotechnology concepts through the eco-enzyme production project, thereby supporting the development of 21st-century skills. The study recommends the use of SETS-based e-modules as a contextual, innovative, and applicable alternative to traditional learning in science education.